Management of fruit species in urban home gardens of Argentina Atlantic Forest as an influence for landscape domestication - Furlan, Violeta (2017)
Home gardens are considered germplasm repositories and places for experimentation, thus they are key sites for the domestication of plants. Domestication is considered a constant process that occurs along a continuum from wild to managed to domesticated populations. Management may lead to the modification of populations and in other cases to their distribution, changing population structure in a landscape. Our objective is focused on the management received in home gardens by perennial species of fruits. For this, the management practices applied to native and exotic perennial fruits species by a group of 20 women in the periurban zone of Iguazú, Argentina, were analyzed. In-depth interviews were conducted, as well as guided tours for the recognition and collection of specimens of species and ethnovarieties. Sixty-six fruit species managed in the home gardens were recorded. The predominant families are Rutaceae, Myrtaceae, and Rosaceae. The fruit species with the highest number of associated management practices are pitanga (Eugenia uniflora) and pindó (Syagrus rommanzoffiana). The 10 species with the highest management intensity are (in decreasing order of intensity) banana (Musa x paradisiaca), palta (Persea americana), pitanga (E. uniflora), mango (Mangifera indica), cocú (Allophylus edulis), mamón (Carica papaya), guayaba (Psidium guajava), limón mandarina (Citrus x taitensis), güembé (Philodendron bipinnatifidum), and mandarina (Citrus reticulata). Among the families with the greatest modifications in their distribution, abundance and presence of ethnovarieties in domestic gardens, are the native Myrtaceae and the exotic Rutaceae. The main management practices involved are cultivation, tolerance, transplant and enhancement in decreasing order. It can be concluded that in Iguazú, fruit species management shows both in plant germplasm as in environment a continuum that through tolerance, transplant and cultivation latu sensu has derived in a mosaic of species in different management situations, which in turn are representative of an anthropogenic landscape in constant domestication and change.